The Impact of Dynamic Managerial Capabilities on Response Strategies to Disruptive Innovation: The Mediating Role of Unlearning and Moderating Role of Managerial Discretion - MADI-ODEH, RANA B. S. (2023)
This thesis utilizes the upper echelon theory, and dynamic capability view of the firm, to address the impact of dynamic managerial capabilities (i.e., managerial human capital, managerial social capital, and managerial cognition) on response strategies to disruptive innovation (i.e., adaptive, and defiant resistant response strategies) in established professional service firms operating in the Emirate of Dubai. Additionally, it tested the impact of individual and organizational unlearning as serial mediators, and managerial discretion as a moderator, on the above-mentioned relation. Adopting a philosophy inclined to positivism, this deductive and quantitative investigation followed a survey strategy, and employed questionnaire as a data collection tool. The questionnaire was established based on adopted measures from previous literature, pre-tested and piloted, before final data collection commenced to its total count of (491) responses. Utilizing (IBM-SPSS 26.0) and (IBM- Amos 23.0), data were analyzed through covariance-based structural equation modelling technique (SEM). The findings of this investigation revealed interesting, and somehow unexpected insights. Contrary to the expectations, managerial human capital indicators (i.e., experience, education, and training) failed to predict for any of the identified response strategies. However, managerial social capital indicators (i.e., social capital from relations with government and community leaders, and social capital from relations with top managers at other business firms) had contrasting results. While the first indicator was expected to predict adaptive response strategies, it did not. Rather, it predicted for defiant resistant strategy. The second indicator successfully predicted the adaptive response strategy, as hypothesized. Finally, managerial cognition indicators (opportunity, and threat cognitive perceptions) played their hypothesized role in relation to response strategies, where opportunity cognitive perception predicted adaptive strategy adoption, and threat cognitive perception predicted the defiant resistant. Unlearning (individual and organizational) significantly and serially mediated the significant identified relations. Managerial discretion was not moderating it. This study contributes in many ways to theory and practice. Theoretically, new insights have been retrieved on the applicability of the upper echelon theory in the research context. A contribution is made in terms of partially unpacking the relational black box of the theory. The study also provided interesting insights on the somehow taken for granted significance of the dynamic managerial capabilities (i.e., managerial human capital, and managerial social capital) and the role they play in responding to disruptive innovation. It also contributed to the enrichment of the literature on upper echelon theory, dynamic managerial capabilities, and disruptive innovation, by providing an empirical and quantitative evidence which the literature lacks, as it highlighted the role of endogenous factors (i.e., dynamic managerial capabilities) in predicting strategic behaviour of established firms (i.e., response strategies to disruptive innovation). It has also emphasized that established firms do respond to disruptive innovation, contrary to the common argument of established firms’ lack of response. Practically, this study provides important empirically supported insights for managers and practitioners regarding the impact of dynamic managerial capabilities on response strategies to disruptive innovation adopted by established firms. In addition to those responsible for developing and selecting executives in organizations, it provides empirical evidence on which capability might affect adaptive response strategies the most. The findings of this study are of significance to policy makers too, who might need to re-look into their requirements if creative economy and innovation are being pursued.